BH4 improves postprandial endothelial function after a high-fat meal in men and postmenopausal women. Issue 5 (May 2017) - Shah, Yashesh; Bass, Leon; Davison, Gareth W.; Seigler, Nichole; Pollock, Jennifer S.; Thomas, Jeff; Harris, Ryan A.
Abstract: Objective: The timing and duration of menopause is important when evaluating the risk for cardiovascular disease in postmenopausal women, likely related in part to nitric oxide (NO) bioavailability. The flow-mediated dilation (FMD) test is a noninvasive assessment of NO bioavailability in humans, and tetrahydrobiopterin (BH4) is essential for NO synthesis. A high-fat meal (HFM) has been used to increase lipemia and reduce NO bioavailability. Thus, this study sought to determine if menopausal transition has any impact on the postprandial endothelial function response to a HFM, and evaluate the effect of BH4 on postprandial endothelial function in postmenopausal women and men. Methods: Utilizing a randomized, double-blind, placebo-controlled design, sex-steroid hormones and FMD were determined in 30 older adults (10 postmenopausal women aged below 3 y [W < 3], 10 postmenopausal women aged above 10 y [W > 10], and 10 men) at baseline and 4 hours after the ingestion of a HFM alone or a HFM with BH4 (HFM + BH4; 5 mg/kg). Results: Data are presented as mean ± SEM. Independent of treatment, postprandial testosterone was significantly ( P  < 0.05) decreased in men (−64 ± 11 ng/dL), whereas no changes were observed in W < 3 or W > 10 group. In addition, concentrations of progesterone were higher ( P  = 0.019) and the testosterone/estradiol ratio was lower ( P  = 0.026) in all groups after the ingestion of HFM + BH4 compared with the ingestion of HFM alone. Overall, an increase in FMD was observed after the ingestion of HFM + BH4 (Δ1.9% ± 0.6%), whereas no change in FMD was observed after the ingestion of HFM alone (Δ−0.7% ± 0.6%). Conclusions: Co-ingestion of BH4 with a HFM not only alters the sex-steroid hormone ratio, it improves postprandial FMD after a HFM regardless of postmenopause status or sex.